Pengaruh Latihan Pasrah Diri Terhadap Tingkat Stres dan Kadar Gula Darah pada Pasien Diabetes Melitus Tipe 2 di Rumah Sakit PKU Muhammadiyah Yogyakarta - Susanti E (Universitas Muhammadiyah Yogyakarta, 2014)
Latihan Pasrah Diri is one of the nursing measurement that can be used by patients with type 2 diabetes mellitus. That measurement can reduce stress levels and blood sugar levels. The adjective of this study was to identify the eff ect of Latihan Pasrah Diri to the stress levels and blood sugar levels in patients with type 2 diabetes mellitus in PKU Muhammadiyah Hospital of Yogyakarta. This research is a quantitative study that using a quasi experimental design and design of pre - post test control group approach. Amount of the sample were 40 respondents, consist of 20 respondents as the intervention group that were given hospital treatment and Latihan Pasrah Diri 2 times/day for 15 minutes for 3 days, and 20 respondents as a control group who received hospital treatment. Sampling methode used was random sampling. T-test was used to examine the diff erence in average stress levels, vital signs (blood pressure, pulse rate and breath) and blood sugar levels in the intervention group and the control group. The results show the average stress levels and blood sugar levels after the LPD intervention in the intervention group were greater than the control group ( p value 0.05 ). The conclusion is that LPD can aff ect stress levels and blood sugar levels of patients with type 2 diabetes mellitus in PKU Muhammadiyah Hospital of Yogyakarta.Keywords : Stress Levels, Blood Sugar Levels, Latihan Pasrah Diri, Type 2 Diabetes Mellitus